Analysis of College of American Pathologists von Willebrand Factor Proficiency Testing Program - Salazar, Eric; Long, Thomas A.; Smock, Kristi Johnson; Wool, Geoffrey D.; Rollins-Raval, Marian; Chen, Dong; Harris, Neil Selwyn; Chan, Clarence W.; Olson, John D.; Pham, Huy P.; Ritter, Jacob; Unold, David; VanSandt, Amanda Matzke; Goodwin IV, Andrew Jackson (Seminars in Thrombosis and Hemostasis, 2022)
Von Willebrand factor (VWF) level and/or function is altered in von Willebrand disease (VWD), the most common heritable bleeding disorder worldwide. Laboratory assessment of VWF is continually evolving. Historically, the primary method for the assessment of VWF platelet-binding activity was the ristocetin cofactor assay (VWF:RCo). Contemporary alternative measures of VWF platelet-binding activity include VWF:GPIbR (recombinant; using ristocetin), VWF:GPIbM (recombinant; gain-of-function mutant), and monoclonal antibody. Recently, the American Society of Hematology, International Society on Thrombosis and Haemostasis, National Hemophilia Foundation, and World Federation of Hemophilia collaboration issued guidelines recommending the use of newer assays of VWF platelet-binding activity (VWF: GPIbM, VWF: GPIbR) over VWF:RCo, given known limitations of the VWF:RCo assay. Despite this recommendation, the newer VWF:GPIbM and VWF:GPIbR assays are not United States Food and Drug Administration cleared, limiting their availability in the United States. We sought to assess assay utilization trends, agreement of VWF testing methods, and imprecision of VWF testing (based on assigned sample type) from the College of American Pathologists Proficiency Testing Surveys. The analysis confirms that, while VWF antigen testing has low imprecision, the various VWF activity assays have significant interassay variability, with VWF:RCo showing greater imprecision than the newer GPIb-binding assays. The overall trends in assay utilization reflect the barriers to complete compliance with modern VWD diagnostic guidelines in North America.
Keywords: von Willebrand disease; coagulation special testing; proficiency testing